Investigation of synthetic clay court`s response under cyclic loading - Papadopoulou, P.; Karlsteen, M.; Gustafsson, M.; Hulthén, E. (Proceedings, 2018)
The synthetic clay tennis court`s properties need to be examined and modified to converge towards the playing characteristics of the natural clay tennis court. The aim of this study was to investigate the responses of three distinct carpet-material combinations and evaluate how the materials` alteration affected the results. The specimens were compressed uniaxially up to 2 kN at 400 N/s loading rate at varying number of cycles. Energy transformation, strain accumulation, step of strain accumulation and moduli of each surface combination were calculated. Results indicated that the measurements were affected by the loading history and that the carpet modification influenced mainly the energy transformation and the strain accumulation, while the material change affected additionally the moduli of the system. Conduction of the experiments enhanced understanding of the clay court`s response and could attribute to the initial modelling of the synthetic clay surface.